Pregnenolone Inhibits Osteoclast Differentiation and Protects Against Lipopolysaccharide-Induced Inflammatory Bone Destruction and Ovariectomy-Induced Bone Loss - Sun, Xiaochen; Zhang, Chenxi; Guo, Huan; Chen, Jiao; Tao, Yali; Wang, Fuxiao; Lin, Xixi; Liu, Qian; Su, Li; Qin, An (Frontiers in Pharmacology, 2020)
Osteolytic bone disease is characterized by excessive osteoclast bone resorption leading to increased skeletal fragility and fracture risk. Multinucleated osteoclasts formed through the fusion of mononuclear precursors are the principle cell capable of bone resorption. Pregnenolone (Preg) is the grand precursor of most if not all steroid hormones and have been suggested to be a novel anti-osteoporotic agent. However, the effects of Preg on osteoclast biology and function has yet to be shown. Here we examined the effect of Preg on RANKL-induced osteoclast formation and bone resorption in vitro, and potential therapeutic application in inflammatory bone destruction and bone loss in vivo. Our in vitro cellular assays demonstrated that Preg can inhibit the formation of TRAP+ve osteoclast formation as well as mature osteoclast bone resorption in a dose-dependent manner. The expression of osteoclast marker genes CTSK, TRAP, DC-STAMP, ATP6V0d2, and NFATc1 were markedly attenuated. Biochemical analyses of RANKL-induced signaling pathways showed that Preg inhibited the early activation of ERK MAPK and NF-κB, which consequently impaired the downstream induction of c-Fos and NFATc1. Using reactive oxygen species (ROS) detection assays, we found that Preg exhibits anti-oxidant properties inhibiting the generation of intracellular ROS following RANKL stimulation. Consistent with these in vitro results, we confirmed that Preg protected mice against local LPS-induced inflammatory bone destruction in vivo by suppressing osteoclast formation. Futhermore, we did not find any observable effect of Preg on osteoblastogenesis and mineralization in vitro. Finally Preg was administered to OVX-induced bone loss and demonstrated that Preg prevented systemic OVX-induced osteoporosis. Collectively, our observations provide strong evidence for the use of Preg as anti-osteoclastogenic and anti-resorptive agent for the potential treatment of osteolytic bone conditions.